Key Technology and Development Trend of Permanent Magnet Motor Traction System for Rail Transit - FENG Jianghua (机车电传动)
The characteristics and advantages of permanent magnet motor traction system in rail transit were introduced. The development status of permanent magnet motor traction system in rail transit at home and abroad was summarized. The key technologies needed to be tackled in the field of rail transit were described in detail. Finally, the development trend of permanent magnet traction system was prospected.